Systemic Inflammation Response Index is a Prognostic Risk Factor in Patients with Hepatocellular Carcinoma Undergoing TACE - Wang TC; An TZ; Li JX; Pang PF (Dove Medical Press, 2021)
Tian-Cheng Wang,1,2 Tian-Zhi An,3 Jun-Xiang Li,4,* Peng-Fei Pang1,* 1Department of Interventional Medicine, The Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong, People’s Republic of China; 2Department of Radiology, The Second Xiangya Hospital of Central South University, Changsha, Hunan, People’s Republic of China; 3Department of Interventional Radiology, The Affiliated Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 4Department of Interventional Radiology, The Affiliated Cancer Hospital of Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Peng-Fei Pang; Jun-Xiang Li Email pangpf@mail.sysu.edu.cn; 357936984@qq.comBackground: Mounting evidence has shown that systemic inflammation response index (SIRI), a novel prognostic biomarker based on peripheral lymphocyte, neutrophil and monocyte counts, is associated with poor prognosis for several tumors. However, the prognostic value of SIRI in patients with hepatocellular carcinoma (HCC) undergoing transarterial chemoembolization (TACE) is elusive. Herein, we aimed to evaluate the correlation between SIRI and clinical outcomes in these patients.Methods: A total of 194 consecutive patients who underwent TACE were included in this study. Patients were stratified into high and low SIRI groups based on the cut-off value using receiver operating characteristic (ROC) analysis. Independent risk factors for tumor response were analyzed using forward stepwise logistic regression. A one-to-one propensity score matching (PSM) was conducted to compare progression-free survival (PFS) and overall survival (OS) between low and high SIRI patients. The discriminatory power of the combination of number of tumors and SIRI in predicting initial TACE response was evaluated by ROC analysis.Results: Patients were divided into high SIRI (> 0.88) and low SIRI (≤ 0.88) groups. High SIRI (p = 0.003) and more than three tumors (p = 0.002) were significantly related to poorer tumor response. Moreover, the low SIRI group had longer PFS and OS than the high SIRI group (both P < 0.05) before and after PSM. Combination of SIRI and number of tumors can improve the predictive ability to predict initial TACE response with an area under the curve (AUC) of 0.678.Conclusion: Pretreatment peripheral blood SIRI was found to be an independent predictor of tumor response and clinical outcomes in patients with HCC undergoing TACE. Patients with high SIRI may have a poor prognosis.Keywords: systemic inflammation response index, hepatocellular carcinoma, transarterial chemoembolization, biomarker, survival